Diversity and ecological drivers of fish in Singkil Swamp Wildlife Reserve, Aceh, Indonesia - NUR ROHIM; SULISTIONO SULISTIONO; FREDINAN YULIANDA; AHMAD MUHTADI (Society for Indonesian Biodiversity, 2024)
Abstract. Rohim N, Sulistiono, Yulianda F, Muhtadi A. 2024. Diversity and ecological drivers of fish in Singkil Swamp Wildlife Reserve, Aceh, Indonesia. Biodiversitas 25: 2849-2856. Singkil Swamp Wildlife Reserve (SSWR) is a conservation area in Aceh Singkil District, Aceh, Indonesia, that has an important role in maintaining the sustainability of fisheries resources on the Singkil coast. This study analyzes fish biodiversity and ecological factors influencing fish distribution in SSWR waters. The data were collected at five stations (Station I and II in the watershed area while Station III, IV, and V in peat swamp area) every month from April to October 2021 (7 months), consisting of fish biodiversity and aquatic ecological characteristics. The data obtained were analyzed using an index of diversity, evenness, dominance, frequency of presence, and Canonical Correspondence Analysis (CCA). Fish biodiversity in the SSWR utilization area consists of 26 species, including 14 families and 19 genera. Station I (in the Alas-Singkil River) has a higher diversity value and is dominated by the white fish group compared to Stations II, III, IV, and V (in the Lae-Treup River), which the black fish group dominates. Based on ecological characteristics, the distribution of fish species in SSWR is divided into four groups. The first and second groups of fish were positively correlated with high pH and DO, while the third and fourth groups tended to have negative correlation values.